Regional and stock-specific differences in contemporary growth of Baltic cod revealed through tag-recapture data. (5th August 2020) - McQueen, Kate; Casini, Michele; Dolk, Bodo; Haase, Stefanie; Hemmer-Hansen, Jakob; Hilvarsson, Annelie; Hüssy, Karin; Mion, Monica; Mohr, Thomas; Radtke, Krzysztof; Schade, Franziska Maria; Schulz, Norbert; et al.
Abstract: The use of growth estimation methods that depend on unreliable age data has previously hindered the quantification of perceived differences in growth rates between the two cod stocks inhabiting the Baltic Sea. Data from cod tagged in different regions of the Baltic Sea during 2007–2019 were combined, and general linear models were fit to investigate inter-regional (defined as area of release) and inter-stock (assigned to a subset of recaptures using genetic and otolith shape analyses) differences in individual growth. An average-sized cod (364 mm) caught in the western Baltic Sea and assigned to the western Baltic cod stock grew at more than double the rate (145 mm year −1 ) on average than a cod of the same size caught in the eastern Baltic Sea and assigned to the eastern Baltic cod stock (58 mm year −1 ), highlighting the current poor conditions for the growth of cod in the eastern Baltic Sea. The regional differences in growth rate were more than twice as large (63 mm year −1 ) as the stock differences (24 mm year −1 ). Although the relative importance of environmental and genetic factors cannot be fully resolved through this study, these results suggest that environmental experience may contribute to growth differences between Baltic cod stocks.